Development of ‘Website Cerdas’ Media to Accommodate Differentiated Learning Styles of Batik Crafts Class XII Students - Setyawan, Haris; Iriaji, Iriaji (UNDIKMA, 2025)
In class XII IPS 3 at SMAN 1 Pagak, students display diverse learning styles, identified through their activity preferences such as listening to music, playing games, and browsing social media. Batik craft is a crucial subject, especially since students are required to create handwritten batik as part of their practical exam. However, the average score of students in this class is lower compared to other classes, and the teaching method relies solely on textbooks without incorporating technology in line with the TPACK (Technological Pedagogical Content Knowledge) approach. Classroom facilities such as Wi-Fi, projectors, and screens provide an opportunity for the development of a Website-based solution that accommodates various learning styles. The Website development follows Thiagarajan's 4D model, which includes four stages: define,Design, develop, and disseminate. Validation results from media experts show a feasibility score of 86.6% (very feasible), while subject matter experts gave a score of 87.5% (very feasible). A small group trial produced a score of 84.8% (very feasible) and an N-Gain value of 0.755 (very effective), demonstrating that the Website, which adapts to students’ learning styles, is effective in enhancing their understanding of batik craft material for class XII IPS 3 students at SMAN 1 Pagak